Perception and use of youtube by music lecturers and librarians in selected tertiary institutions in Kwara State, Nigeria (2018)
This study examined the music lecturers and librarians use and perception of YouTube in selected Kwara State tertiary institutions. Survey approach was adopted to conduct the study. The sample comprised 35 respondents (20 librarians and 15 music lecturers). Three research questions were answered while data were analyzed using percentage, frequency count, and cross tabulation. YouTube was used by the music lecturers mostly for teaching, research and learning, enhancing learning experience, and engaging students with the contents of music lessons. Librarians on the other hand use YouTube mostly as reference point for events and occurrences, teaching tool for library instruction; and for communicating other libraries.